Can virtue contextualism resolve the Gettier problem? - Du, Racher Jiaqi (Nanyang Technological University, 2021)
The Gettier problem is one of the main challenges an epistemological theory of knowledge has to overcome. In the recent debate, contextualism and virtue epistemology have been one of the few contending views on knowledge as well as epistemological methodology. This paper seeks to examine the viability of virtue contextualism against the Gettier problem. Focusing on refining John Greco’s version of virtue contextualism which is grounded by a theory of intellectual credit, the essay evaluates its critics’ objections such as Dirk Koppelberg’s argument that Greco’s virtue contextualism cannot resolve the lottery problem and Jennifer Lackey’s paper, “Why We Don’t Deserve Credit for Everything We Know” in which she argues that intellectual credit is insufficient for knowledge given that knowledge does not always require credit. At the end of the evaluation, the paper maintains that Greco’s virtue contextualism (1) remains sufficient for knowledge if it can include a plurality of intellectual virtues that includes both cognitive faculties and character traits, and (2) it can resolve some Gettier cases.